The Effect of Human Development on Poverty in Bangka District 2011-2020 - Zakiyudin Fikri; Hattami Amar (Yayasan Ilomata, 2023)
The purpose of this study was to determine whether there was an effect of human development on poverty in Bangka Regency in 2011-2020 and how big the effect was. The locus of this research is in Bangka Regency. This type of research is quantitative with an associative approach with a simple linear regression analysis model. The feasibility test of the regression model uses the classical assumption test, and the t test to see the significance of the effect. The results showed that human development had a negative but not significant effect on poverty in Bangka Regency. The magnitude of the influence of human development on poverty is only 36.9 percent, the remaining 63.1 percent is influenced by other variables not included in this study. Simple linear regression equation Y = 13.839 – 0.122 X, regression coefficient value -0.122, meaning that if Human Development with the Human Development Index indicator increases by 1 point, then the poverty rate in Bangka Regency is predicted to decrease by 0.122 percent. Recommendation to the government of Bangka Regency is that in development planning to utilize the results of research or research, especially research related to the influence of human development on poverty. The allocation of funds related to human development needs to be evaluated, so that it is more targeted in alleviating poverty in Bangka Regency, because in reality it has no significant effect on reducing poverty in terms of the 2011-2020 data series.